2021
DOI: 10.1101/2021.05.25.21257803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SELP Asp603Asn and severe thrombosis in COVID-19 males: implication for anti P-selectin monoclonal antibodies treatment

Abstract: Thromboembolism is a frequent cause of severity and mortality in COVID-19. However, the etiology of this phenomenon is not well understood. A cohort of 1,186 subjects, from the GEN-COVID consortium, infected by SARS-CoV-2 with different severity were stratified by sex and adjusted by age. Then, common coding variants from whole exome sequencing were mined by LASSO logistic regression. The homozygosity of the cell adhesion molecule P-selectin gene (SELP) rs6127 (c.1807G>A; p.Asp603Asn) which increases platel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Many more genes are expected to be involved in COVID-19 than the dozens reported thus far. These genes are likely to include a relatively small number of Frontiers in Genetics frontiersin.org core genes and a much larger number of peripheral genes carrying both common and rare variants (Fallerini et al, 2022;Zguro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many more genes are expected to be involved in COVID-19 than the dozens reported thus far. These genes are likely to include a relatively small number of Frontiers in Genetics frontiersin.org core genes and a much larger number of peripheral genes carrying both common and rare variants (Fallerini et al, 2022;Zguro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, rs6127 is mapped to the SELP gene, which codes for selectin P, a cell adhesion molecule (146). In a recent whole exome sequencing study, the polymorphism was found to be associated with thrombosis and COVID-19 severity in male patients (147). Overall, the COVID-19 related SNPs which fall into the cluster of high allele frequency are located in varying genomic regions, from introns and exons to intergenic regions.…”
Section: Resultsmentioning
confidence: 99%
“…At the contrary, machine learning (ML) approaches offer an innovative tool for managing complex problems by significantly increasing our capacity to identify complex patterns of variations. Using data from the whole exome sequencing (WES), a first line of the ML method, i.e., a LASSO logistic regression, has been applied to extract some thousands of coding genetic features contributing to COVID-19 severity Picchiotti et al (2021); Fallerini et al (2022). Subsequent functional validation of extracted features demonstrated that, in each tested case, the association with severity has a biological basis and suggested hints for adjuvant treatment Benetti et al (2020b); Fallerini et al (2021b,a); Croci et al (2022); Baldassarri et al (2021b,a); Mantovani et al (2022); Monticelli et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent functional validation of extracted features demonstrated that, in each tested case, the association with severity has a biological basis and suggested hints for adjuvant treatment Benetti et al (2020b); Fallerini et al (2021b,a); Croci et al (2022); Baldassarri et al (2021b,a); Mantovani et al (2022); Monticelli et al (2021). Using the extracted features, Fallerini et al (2022) build a severity score named the integrated polygenic score (IPGS), whose performances reached about 75% for both sensitivity and specificity. In this contribution, we want to improve the IPGS severity score performances, with the aim of increasing both metrics and the understanding of biomolecular mechanisms for personalized treatment using innovative ML methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation